Tetrapod diversity in the Atlantic Forest: Maps and gaps - de Souza Lima Figueiredo, Marcos; Weber, Marcelo M.; Brasileiro, Cinthia Aguirre; Cerqueira, Rui; Grelle, Carlos E. V.; Jenkins, Clinton N.; Solidade, Caroline V.; Thomé, Maria Tereza Chiarioni [UNESP]; Vale, Mariana Moncassin; Lorini, Maria Lucia (Springer Nature, 2021)
The Atlantic Forest is a heterogeneous and complex vegetation mosaic caused by variety of climatic, geomorphological, and edaphic conditions. It has long been known that the Atlantic Forest has one of the most diversified biotas on the planet, presenting high levels of endemism. Here, we update the knowledge regarding terrestrial vertebrates occurring in the Atlantic Forest, focusing on endemic species and presenting its main spatial patterns of diversity. We also analyzed the main knowledge gaps associated with these species. We identified 2,645 species of Tetrapoda in the Atlantic Forest, being 719 species of amphibians, 517 species of reptiles, 1,025 species of birds, and 384 species of mammals. The uniqueness of its fauna is impressive even in a global scale, as 2.8% of the world's Tetrapoda species occurs only in the Atlantic Forest. For reptiles, this percentage is 1.3%, while for both birds and mammals, it hovers around 1.9%, but for amphibians, it reaches an impressive 6.6%. Spatially, most groups exhibit their highest species richness at the core of the Atlantic Forest, and this pattern becomes more evident when only endemic species are considered. Even with all its impressive diversity, 157 new Tetrapoda species were described in the Atlantic Forest in the last decade, mostly from poorly sampled regions or environments. An increase of sampling effort on these regions might increase the number of species on this biome, which already is one of the most diverse in the world.
Keywords: Endemism; Linnean shortfall; Richness; Spatial patterns; Wallacean shortfall